POLA KONSUMSI ENERGI, PROTEIN, PERSEN LEMAK TUBUH DAN AEROBIC ENDURANCE ATLET RENANG REMAJA - Muhammad Mukhdor Al Faruq; Sri Adiningsih (Universitas Airlangga, 2015)
Teenagers swimming athlete has higher nutrient requirement than most teenagers with the same age to support their growth and their sport activity. Swimming athletes are required to have good body composition for maximum performance. The aim of this research was to measure macronutrient consumption, percent body fat, and aerobic endurance of teenager swimming athlete. This research was an observational descriptive using cross-sectional study design with 23 swimming athletes who have minimum age of 10 years and having minimum one regency-stagecompetition attended. The data collected by interviewer, include characteristics, food consumption by 2x24 hours food recall, body fat percentage by Bioelectrical Impedance Analysis, and aerobic endurance by Critical Swim Speed Test. The result showed that energy intake was 2394.8 ± 780 kcal in male athlete and 2125.9 ± 336.6 kcal in female athlete,protein consumption was 108.4 ± 38.5 gram in male athlete and 85.1 ± 23.9 gram in female athlete. Body fat was 17.8 ± 6.7% in male athlete and 24.1 ± 7.3% in female athlete and critical swim speed was 1.05 ± 0.17 m/s in male athlete and 1.06 ± 0.12 m/s in female athlete. It is concluded that energy intake and protein consumption had fulﬁ lled standard of swimmers need. Body fat level was higher than swimmers standard. The mean of CSS was 1,05 ± 0,15 m/s. Therefore, athlete should maintain their diet and increase their exercise.Keywords: aerobic endurance, swimming athlete, energy intake, protein intake, body fat